Análise do atravessamento dos arcabouços teóricos e práticos dos multiletramentos e da decolonialidade nas práxis pedagógicas de um projeto antirracista alicerçado pela Lei nº 10.639/03 - Bezerra, Kátia Alves (2023)
This research intends to analyze how an African culture and games project is based on the law 10.639/03 and is crossed by the theoretical and practical frameworks of Multiliteracies and decoloniality. The central issue of the work can be described in the following terms: How decoloniality, multiliteracies and the demands of Law nº 10.639/03 cross a project of anti-racist practices for the critical racial literacy (CRL) of students and educators of a school Municipal Elementary School (EMEF) in São Paulo? The search for answers to such questioning will be through critical research with a qualitative approach. The data will be obtained through the analysis of pedagogical practices inserted in a didactic project organized by an arts teacher in partnership with teachers of the fifth year of elementary school that materialized in an EMEF in the northwest region of the municipality of São Paulo and through interviews semi-structured and audiovisual materials published on the web and data found in PortalEduca and Escola online (EOL) portals. The theoretical references to be researched for multiliteracies will be LIBERALI (2009, 2012, 2020), NEW LONDON GROUP (1996), STREET (2014) and ROJO (2013) which converged to the LRC studies that will be based by FERREIRA (2014, 2015). For the reasoning regarding decoloniality, authors from the Modernity/Coloniality group will be used, such as CASTRO-GÓMEZ (2007), GROSFOGUEL (2007) and MIGNOLO (2015, in addition to documents such as the Federal Constitution 1988 and laws 10.639/03 and 11.645/08. Data analysis was carried out through critical reflection actions: describing what it is to report the concrete facts so that one can understand what underlies actions in the classroom, informing that resuming some fundamental concepts and theories for teaching and learning, confront questioning theories and practices within the socio-historical-cultural context and the reconstruction that seeks to transform pedagogical practices through critical reflection (SMYTH, 1992). After confronting it, through reflection, the paths and paths taken in the action and the possibilities of tuning are rethought. This step is to reconstruct the project to be used in the same or another context. Therefore, based on the findings of the analysis and reflection, a new training proposal will be elaborated to be suggested in another school unit, seeking increasingly potent anti-racist practices. The results confirmed that anti-racist practices crossed by law 10.639/03, by Multiliteracies and by deloconiality, favored critical racial literacy, that is, in the process of transformation of subjects, allowing the development of a critical stance in the face of combating racism, however., in addition to these crossings, it is important that there is a transformation of the agents for a purposeful and engaged action